2017
DOI: 10.1590/1518-8345.2345.2974
|View full text |Cite
|
Sign up to set email alerts
|

Risk classification priorities in an emergency unit and outcomes of the service provided

Abstract: Objective:to check the association of the proposed priorities of the institutional protocol of risk classification with the outcomes and evaluate the profile of the care provided in an emergency unit. Method:observational epidemiological study based on data from the computerized files of a Reference Emergency Unit. Care provided to adults was evaluated regarding risk classification and outcomes (death, hospitalization and hospital discharge) based on the information recorded in the emergency bulletin. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
4
1
3
Order By: Relevance
“…The mortality rate in the sample was substantially higher than those found in the literature ( 8 , 14 ) . However, it is worth noting that the sample was composed only of patients who reported severity when they arrived at the emergency service and, therefore, were potentially more serious than the general population seeking ED, frequently investigated in other studies.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The mortality rate in the sample was substantially higher than those found in the literature ( 8 , 14 ) . However, it is worth noting that the sample was composed only of patients who reported severity when they arrived at the emergency service and, therefore, were potentially more serious than the general population seeking ED, frequently investigated in other studies.…”
Section: Discussioncontrasting
confidence: 72%
“…As for the death outcome, the two systems showed similar values in most of the analyses performed. Researchers who investigated the triage given by an institutional protocol with the outcomes of patients seen at an emergency unit in the inland of São Paulo identified that, among the patients considered severe, the death rate corresponded to 66.7% and, in the group of low priority of care, this rate was 1.7% ( 14 ) . There was also a group of patients who were not classified by the institutional protocol due to situations of extreme severity and, therefore, were referred directly to the emergency room, where they had a death rate of 31.4% ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the red category had a higher percentage of deaths. Research that correlated RS categories with the outcomes of care also found a higher occurrence of deaths in high-priority patients (7,18,37) . Another study (17) also found that MTS is a good predictor of death, i.e., the greater the severity of patients, the greater the chance of dying.…”
Section: Discussionmentioning
confidence: 94%
“…Segundo os autores, a utilização dos serviços de emergências pela população não reflete emergências. Entende-se que elas estejam ligadas à compreensão de utilização desses serviços, como uma porta qualificada de acesso ao sistema de saúde, desconsiderando a ABS, nicho destinado a absorver a demanda de baixa complexidade 28. ConclusãoOs resultados indicam diferenças geracionais e de gênero na utilização do serviço e evidencia o comportamento sazonal de utilização entre os dias da semana.…”
unclassified